The Emergence of Open-Source Software in North America - Pan, Guohua; Bonk, Curtis J. (International Review of Research in Open and Distributed Learning, 2007)
Unlike conventional models of software development, the open source model is based on the collaborative efforts of users who are also co-developers of the software. Interest in open source software has grown exponentially in recent years. A Google search for the phrase open source in early 2005 returned 28.8 million webpage hits, while less than two years later that number had jumped to 376 million. This paper discusses the origin of the term open source and the key tenets of the open source software development model. In addition, it analyzes the merits and drawbacks of using this model and discusses the advantages and disadvantages of applying the model in higher education. Importantly, examples are provided of computer software, and course management systems in particular, developed using the open source model. Also included are brief analyses of the Linux operating system, and two open source course management systems, Sakai and Moodle, as well as the uPortal. A timeline of major open source projects of significance in North America is provided. The paper concludes with a discussion of the potential for applying the open source software development model to open and distance education.